(x+6)*(n+6-10)=100

Simple and best practice solution for (x+6)*(n+6-10)=100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+6)*(n+6-10)=100 equation:


Simplifying
(x + 6)(n + 6 + -10) = 100

Reorder the terms:
(6 + x)(n + 6 + -10) = 100

Reorder the terms:
(6 + x)(6 + -10 + n) = 100

Combine like terms: 6 + -10 = -4
(6 + x)(-4 + n) = 100

Multiply (6 + x) * (-4 + n)
(6(-4 + n) + x(-4 + n)) = 100
((-4 * 6 + n * 6) + x(-4 + n)) = 100
((-24 + 6n) + x(-4 + n)) = 100
(-24 + 6n + (-4 * x + n * x)) = 100

Reorder the terms:
(-24 + 6n + (nx + -4x)) = 100
(-24 + 6n + (nx + -4x)) = 100
(-24 + 6n + nx + -4x) = 100

Solving
-24 + 6n + nx + -4x = 100

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 6n + nx + 24 + -4x = 100 + 24

Reorder the terms:
-24 + 24 + 6n + nx + -4x = 100 + 24

Combine like terms: -24 + 24 = 0
0 + 6n + nx + -4x = 100 + 24
6n + nx + -4x = 100 + 24

Combine like terms: 100 + 24 = 124
6n + nx + -4x = 124

Add '4x' to each side of the equation.
6n + nx + -4x + 4x = 124 + 4x

Combine like terms: -4x + 4x = 0
6n + nx + 0 = 124 + 4x
6n + nx = 124 + 4x

Reorder the terms:
-124 + 6n + nx + -4x = 124 + 4x + -124 + -4x

Reorder the terms:
-124 + 6n + nx + -4x = 124 + -124 + 4x + -4x

Combine like terms: 124 + -124 = 0
-124 + 6n + nx + -4x = 0 + 4x + -4x
-124 + 6n + nx + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
-124 + 6n + nx + -4x = 0

The solution to this equation could not be determined.

See similar equations:

| y=2.9x+6.3 | | 3x-9-(x+1)2=54 | | 3ln(4x-1)+13=34 | | 7-xy+7x-(-10)+5xy-3x= | | s/3-3/s | | 500=x-50 | | x^2-3x+2x^2-x=3x^2-6x-3 | | 7-sy+7x-(-10)+5xy-3x= | | 5x-15/5x | | 3x=2x+7.5 | | 3q^2-36q+750=0 | | 8x+4-x=-3-2x-11 | | 9a-2-2a+3= | | 18a+(2b-4a)= | | y^2-3.3y-10=0 | | 3(2x+5)+8=4(x-1) | | 8x=6x+26 | | 26+6x=8x | | 3x^2-18x+750=0 | | a^2x+ax+6a=a^2+12a+9 | | Y=103-2x | | 150+3x=x+300-t | | 6*h=8*2 | | 2x/5-5 | | 2x-6x+12=36 | | x-(0.08x)=500 | | (25b-5)-6(4b+3)=-6 | | (25b-5)-6(4b+1)=-6 | | 7x+x=12+8 | | (12m)/4 | | 4x+14=-99+10x | | x-((8/100)*x)=500 |

Equations solver categories